FCNC, CP Violation and implications for some rare decays in a model with gauge symmetry 3-4-1 (2011)
Models with gauge symmetry SU(3)c SU(4)L U(1)Y (3-4-1 models) where anomaly cancellation takes place between families (three-family models) predict the existence of new heavy neutral gauge bosons which transmit flavor changing neutral currents at tree-level. In this work, in the context of a three-family 3-4-1 model which do not contain particles with exotic electric charges, we analyze the constraints coming from neutral meson mixing on the parameters of the model. Taking into account the experimental measurements of observables related to K and B meson mixing and including CP-violating phases, we study the resulting bounds for angles and phases in the mixing matrix for the down-quark sector, as well as the implications of these bounds for the modifications of some rare decays, namely K^+ →π^+ ¯v v.K_L→π^0 v¯v,K_L→π^0 l^+ l^- and B_(d⁄s)→μ^+ μ^-